The effect of curing units and methods on degree of conversion of two types of composite resins - Hasani Tabatabaei M; Mirzaei M; Ataei M; Motevaselian F (Tehran University of Medical Sciences, 2007)
Background and Aim: Halogen lamp is the commonly used light source for composite photo polymerization. Recently, high power halogen lamps, LED and plasma arc are introduced for improving the polymerization. The aim of this study was to investigate the effect of conventional and high power halogen lamps and LED light curing unit on degree of conversion of two different composite resins.Materials and Methods: In this in vitro experimental study two halogen units (Coltolux 50 with the intensity of  330 mW/cm2 and Optilux 501 with two different operating modes of standard with the intensity of 820 mW/cm2 and Ramp with the intentsiy of 100-1030mW/cm2) and one LED light curing unit (620 mW/cm2) were used. The composites were hybrid (Tetric ceram) and nanofilled (Filteke supreme). Each materials/curing method contained three samples and degree of conversion (DC) was measured with FTIR. Data were analyzed statistically with one way and two way ANOVA, Tukey HSD. P<0.05 was considered as the limit of significance.Results: Tetric ceram revealed higher DCthan Supreme. Tetric ceram showed a significant decrease in DC when Coltolux 50 was used in comparison to LED and Optilux 501. The latters did not show significant effect on DC of this material. DC of Supreme polymerized with various curing modes was not significantly different.Conclusion: Based on the results of this study, degree of conversion in hybrid composites was higher than nanofilled. In comparison with conventional halogen lamp (Coltolux 50), high intensity halogen lamps and LED unit significantly lead to higher degree of conversion in hybrid composites.